Craniosynostosis and risk factors related to thyroid dysfunction. (5th February 2015) - Carmichael, S.L.; Ma, C; Rasmussen, S.A.; Cunningham, M.L.; Browne, M.L.; Dosiou, C; Lammer, E.J.; Shaw, G.M.
Abstract : Thyroid disease is a common problem among women of reproductive age but often goes undiagnosed. Maternal thyroid disease has been associated with increased risk of craniosynostosis. We hypothesized that known risk factors for thyroid disease would be associated with risk of craniosynostosis among women not diagnosed with thyroid disease. Analyses included mothers of 1, 067 cases and 8, 494 population‐based controls who were interviewed for the National Birth Defects Prevention Study. We used multivariable logistic regression to estimate adjusted odds ratios (AOR) and 95% confidence intervals (CI). After excluding women with diagnosed thyroid disease, younger maternal age (AOR 0.7, 95% CI 0.6–0.9, for <25 years versus 25–29), black or other race‐ethnicity (AOR 0.3, 95% CI 0.2–0.4 and AOR 0.6, 95% CI 0.4–0.8, respectively, relative to non‐Hispanic whites), fertility medications or procedures (AOR 1.5, 95% CI 1.2–2.0), and alcohol consumption (AOR 0.8, 95% CI 0.7–0.9) were associated with risk of craniosynostosis, based on confidence intervals that excluded 1.0. These associations with craniosynostosis are consistent with the direction of their association with thyroid dysfunction (i.e., younger age, black race‐ethnicity and alcohol consumption are associated with reduced risk and fertility problems are associated with increased risk of thyroid disease). This study thus provides support for the hypothesis that risk factors associated with thyroid dysfunction are also associated with risk of craniosynostosis. Improved understanding of the potential association between maternal thyroid function and craniosynostosis among offspring is important given that craniosynostosis carries significant morbidity and that thyroid disease is under‐diagnosed and potentially modifiable. © 2015 Wiley Periodicals, Inc.